Arbitrary and Independent Polarization Control In Situ via a Single Metasurface. Issue 21 (9th August 2018) - Yan, Libin; Zhu, Weiming; Karim, Muhammad Faeyz; Cai, Hong; Gu, Alex Yuandong; Shen, Zhongxiang; Chong, Peter Han Joo; Tsai, Din Ping; Kwong, Dim‐Lee; Qiu, Cheng‐Wei; Liu, Ai Qun
Abstract: A single metasurface is demonstrated with powerful manipulating capability to arbitrarily and independently tune the phase profiles of orthogonal polarization states using subwavelength tunable cross‐shaped element (TCE) arrays. Here, the arbitrary control of the phase profiles must be distinguished from the semiarbitrary phase control using multiple predesigned metasurfaces with one‐to‐one functionality. The decoupled tuning of phase profiles for orthogonal polarization states bestows the metasurface with additional degree of freedom to manipulate the electromagnetic wave for multifunctionality. As a proof of concept, a tunable polarization beam splitter, a dynamic beam steering component, and a quarter waveplate are demonstrated using one single metasurface. This metasurface has promising applications on versatile and function‐switchable photonic components, such as polarization optical devices, compact functional devices, communication systems, and wave controlling devices, to name just a few. Abstract : Arbitrary and independent polarization control is realized using a single metasurface constituted by tunable cross‐shaped element (TCE), of which the orthogonal resonance modes can be independently tuned. Here, tunable polarization beam splitter, dynamic beam steerer, and quarter waveplate are demonstrated using this single metasurface.